2013
DOI: 10.1038/ncomms2785
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale organic nanowire lithography and electronics

Abstract: Controlled alignment and patterning of individual semiconducting nanowires at a desired position in a large area is a key requirement for electronic device applications. High-speed, large-area printing of highly aligned individual nanowires that allows control of the exact numbers of wires, and their orientations and dimensions is a significant challenge for practical electronics applications. Here we use a high-speed electrohydrodynamic organic nanowire printer to print large-area organic semiconducting nanow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
166
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 268 publications
(173 citation statements)
references
References 29 publications
(49 reference statements)
4
166
0
Order By: Relevance
“…To achieve this functionality, we suggest a patternable and foldable substrate using our CNF hybrid film. Although many previous studies have reported on stretchable interconnects using graphene, 35 metal nanowires, 36 metal nanofiber, 37,38 and geometrical approaches, 39 conventional electronic devices fabricated on the elastomeric substrate are easily broken because most of the semiconductor, dielectric and encapsulation materials are still brittle. Therefore, the approach using origami substrates made of strain-free rigid plates with reversibly foldable and stretchable, elastomeric joints 40 has been considered as a promising strategy for stretchable electronics.…”
Section: Demonstration Of a Transparent Oled On The Hybrid Filmmentioning
confidence: 99%
“…To achieve this functionality, we suggest a patternable and foldable substrate using our CNF hybrid film. Although many previous studies have reported on stretchable interconnects using graphene, 35 metal nanowires, 36 metal nanofiber, 37,38 and geometrical approaches, 39 conventional electronic devices fabricated on the elastomeric substrate are easily broken because most of the semiconductor, dielectric and encapsulation materials are still brittle. Therefore, the approach using origami substrates made of strain-free rigid plates with reversibly foldable and stretchable, elastomeric joints 40 has been considered as a promising strategy for stretchable electronics.…”
Section: Demonstration Of a Transparent Oled On The Hybrid Filmmentioning
confidence: 99%
“…Additionally, unlike conventional drop-on-demand type jet printing technique [10], WDW can print the serpentine patterns in continuous jet mode. Therefore, it is believed that WDW can achieve low cost, high precision fabrication of flexible/stretchable electronics [18,32]. Moreover, we observed that the serpentine structures deposited with different parameters show different structural colors under irradiation of light.…”
Section: Resultsmentioning
confidence: 72%
“…1D nanomaterials, acting as building blocks in miniaturized optoelectronics,1 have attracted great research interests for manipulating photons at micro/nanoscale. Assembling 1D nanowires into complex heterostructures with high spatial and angular precision is critical for realizing various functional devices, including photonic routers,2 logic gates,3 modulators,4 wavelength filters,5 and multiplexers 6.…”
mentioning
confidence: 99%